Performance Evaluation of Warm- and Hot-Mix Asphalt Mixtures Based on Laboratory and Accelerated Pavement Tests. (24th October 2012) - Kim, Yongjoo; Lee, Jaejun; Baek, Cheolmin; Yang, Sunglin; Kwon, Sooahn; Suh, Youngchan
Abstract : A number of warm-mix asphalt (WMA) technologies are used to reduce the temperature at which the asphalt mixtures are produced and compacted, apparently without compromising the performance of the pavement. The main objective of this study is to determine whether the use of an innovative wax-based LEADCAP WMA additive influences the performance of the asphalt mixture, which is produced and compacted at significantly low temperatures. The WMA pavement using LEADCAP additive (WMA-LEADCAP) along with a control HMA pavement was evaluated with respect to their performances of rutting resistance, crack resistance, and viscoelastic property based on the laboratory dynamic modulus test, indirect tensile strength test, and in-door accelerated pavement test (APT) results. With the limited data carried out, the LEADCAP additive is effective in producing and paving asphalt mixture at approximately 30°C lower temperature than a control HMA mixture, and the performances of WMA-LEADCAP pavement are comparable to a control HMA pavement.